The economics and politics of high-speed rail : lessons from experiences abroad - Albalate, Daniel, 1980- (Lexington Books, 2012)
The Economics and Politics of High Speed Rail: Lessons from Experiences Abroad, by Daniel Albalate and Germà Bel, introduces the main questions policy makers and scholars should examine when considering and studying HSR implementation, with particular emphasis on the US's recent interest in this technology and possible application in California. This study is a rigorous investigation of the economic and political challenges and ramifications of implementing new public transportation technology and its effects on taxpayers.</spa.